2018
DOI: 10.1002/jcp.27372
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and pancreatic cancer: Current knowledge and future perspectives

Abstract: Pancreatic cancer has a high mortality rate due to the absence of early symptoms and subsequent late diagnosis; additionally, pancreatic cancer has a high resistance to radio- and chemotherapy. Multiple inflammatory pathways are involved in the pathophysiology of pancreatic cancer. Melatonin an indoleamine produced in the pineal gland mediated and receptor-independent action is the pancreas and other where has both receptors. Melatonin is a potent antioxidant and tissue protector against inflammation and oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 123 publications
0
14
0
Order By: Relevance
“…Pancreatic ductal adenocarcinoma (PDAC) is one of the most common causes of cancer-related deaths worldwide[1]. Currently, the treatment options for patients with inoperable pancreatic cancer are very limited, and the clinical outcomes remain unsatisfactory[2,3]. Although some understanding of the molecular pathogenesis of pancreatic cancer development and progression was obtained[4-6], new therapy targets are necessary to improve the survival rate of pancreatic cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is one of the most common causes of cancer-related deaths worldwide[1]. Currently, the treatment options for patients with inoperable pancreatic cancer are very limited, and the clinical outcomes remain unsatisfactory[2,3]. Although some understanding of the molecular pathogenesis of pancreatic cancer development and progression was obtained[4-6], new therapy targets are necessary to improve the survival rate of pancreatic cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature, structure and function of melatonin, much of this research has focused on hormone-dependent tumors, such as breast and pancreatic cancers [10,11,12]. However, the preventive and therapeutic actions of melatonin have also been observed in many other types of tumors, including oral and esophageal cancers [13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has also the ability to repair cellular damage and protect healthy cells (Kumar et al 2017). Tamtaji et al (2019) reviewed the results of several in vivo and in vitro studies claiming that supplementation with melatonin showed a therapeutic alternative for pancreatic cancer. This effect could be associated with the ability of melatonin to induce the apoptosis of cancer cells, which involves a broad spectrum of molecular mechanisms such as oxidative stress.…”
Section: Accepted Articlementioning
confidence: 99%